Numerical Analysis on Biogenic Emission Sources Contributing to Urban Ozone Concentration in Osaka, Japan - Hiroshi Nishimura; Hikari Shimadera; Akira Kondo; Kazuyo Akiyama; Yoshio Inoue (Asian Journal of Atmospheric Environment, 2015)
This study conducted analyses on biogenic volatile organic compounds (BVOC) emission sources contributing to urban ozone (O3) concentration in Osaka Prefecture, Japan in summer 2010 by using the Weather Research and Forecasting model (WRF) version 3.5.1 and the Community Multiscale Air Quality model (CMAQ) version 5.0.1. This prefecture is characterized by highly urbanized area with small forest area. The contributions of source regions surrounding Osaka were estimated by comparing the baseline case and zero-out cases for BVOC emissions from each source region. The zero-out emission runs showed that the BVOC emissions substantially contributed to urban O3 concentration in Osaka (10.3 ppb: 15.9% of mean daily maximum 1-h O3 concentration) with day-by-day variations of contributing source regions, which were qualitatively explained by backward trajectory analyses. Although O3 concentrations were especially high on 23 July and 2 August 2010, the contribution of BVOC on 23 July (35.4 ppb: 25.6% of daily maximum O3) was much larger than that on 2 August (20.9 ppb: 14.2% of daily maximum O3). To investigate this difference, additional zero-out cases for anthropogenic VOC (AVOC) emissions from Osaka and for VOC emissions on the target days were performed. On 23 July, the urban O3 concentration in Osaka was dominantly increased by the transport from the northwestern region outside Osaka with large contribution of O3 that was produced through BVOC reactions by the day before and was retained over the nocturnal boundary layer. On 2 August, the concentration was dominantly increased by the local photochemical production inside Osaka under weak wind condition with the particularly large contribution of AVOC emitted from Osaka on the day.